Geodetske in teoretične metode določanja pomikov s poudarkom na odkrivanju grobih pogreškov - Kovačič, Boštjan (Geodetski vestnik, 2004)
At the Faculty of Civil Engineering in Maribor, and in cooperation with the company Geoin, structural loading tests for the analysis of materials have been performed over many years. In this paper, an analysis of theoretical and measured values of vertical movements is presented. The loading values, material and concrete properties are calculated for theoretical values. The statically calculated values are confirmed with geodetic methods only. During the measurements, redundancy of observations is requested, therefore in the article the main emphasis is given to the method of detection and elimination of gross errors that have a significant influence on final results.
Keywords: analiza rezultatov; geodesy; geodezija; meritve; metode; pomiki